Suffering quantified? Feasibility and psychometric characteristics of 2 revised versions of the Pictorial Representation of Illness and Self Measure (PRISM) - Wouters EJM; Reimus JLM; van Nunen AMA; Blokhorst MGB; Vingerhoets AJJ (Behavioral Medicine)
The Pictorial Representation of Illness and Self Measure (PRISM) assesses suffering. In this article, the authors explored the feasibility and psychometric qualities of 2 revised versions of the PRISM-PRISM-R1 and PRISM-R2-that they used in 3 studies of participants with different medical problems. The results showed significant differences between the patient groups in suffering as measured with the revised PRISMs. In addition, the revised PRISMs appeared to be sensitive to change in the predicted direction after an intervention. Last, the 2 measures of the revised PRISM seemed to indicate different aspects of suffering. These findings yield preliminary support for the feasibility and validity of the PRISM-R2.